Conceptual Bases of Use of Free Software in the Professional Training of Pre-Service Teacher of Mathematics, Physics and Computer Science - Величко, Владислав; Федоренко, Олена; Кассім, Дар'я (Pedagogy of Higher and Secondary Education, 2018)
Velichko V.Ye., Fedorenko O.G. and Kasím D.A. Conceptual Bases of Use of Free Software in the Professional Training of Pre-Service Teacher of Mathematics, Physics and Computer Science. The development of education is associated primarily with the use of ICT. A significant experience is already gained in how to use educational computer systems while new forms and methods of learning based on modern information technology are being developed and used. In relation to free software, a period when the quantity should translate into quality and an indicator of such translation is development of the concept of the introduction of free software in educational activities of universities. The proposed concept, let’s take Ukraine as an example, determines the main aim of introduction of free software in the training of pre-service of Mathematics, Physics and Computer Science; defines the objectives, measures, principles, the role and value of free software in the informatization process and results of its implementation.